Perkembangan Sastra Arab dan Pengaruhnya Terhadap Bahasa - Naimatul Fuadah; Ainur Rofiq Sofa (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
Arabic literature has undergone significant development from pre-Islamic times to the modern era, reflecting social, cultural and intellectual changes in Arab civilization. Changes in literary works, whether in the form of poetry, prose, or novels, have also influenced the development of the Arabic language in terms of vocabulary, structure, and style of expression. This study aims to analyze how the evolution of Arabic literature impacts the development of the Arabic language by using qualitative research methods. The approach used is descriptive analysis with library research techniques, where data is collected from various sources, such as classical and modern literary works, academic journals, and previous studies that discuss the relationship between literature and language. The results show that Arabic literature plays a role in the formation of modern Arabic through vocabulary enrichment, syntactic innovation, and the spread of various dialects. In addition, the influence of literature on language is also seen in the context of education and mass media. By understanding the close relationship between literature and language, this research is expected to provide new insights for the study of Arabic linguistics as well as the preservation of literary wealth in language development.